2017
DOI: 10.1016/j.advwatres.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Pore-scale supercritical CO2 dissolution and mass transfer under drainage conditions

Abstract: Abstract:Recently, both core-and pore-scale imbibition experiments have shown nonequilibrium dissolution of supercritical CO 2 (scCO 2 ) and a prolonged depletion of residual scCO 2 . In this study, pore-scale scCO 2 dissolution and mass transfer under drainage conditions were investigated using a two-dimensional heterogeneous micromodel and a novel fluorescent water dye with a sensitive pH range between 3.7 and 6.5. Drainage experiments were conducted at 9 MPa and 40 °C by injecting scCO 2 into the sandstone-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Under the experimental conditions (40 °C, 9 MPa), the solubility of scCO 2 dissolved in water is 1.225 mol/L (Spycher and Pruess, 2005). Meanwhile, in previous studies (Chang et al, 2016(Chang et al, , 2017(Chang et al, , 2019, we have showed the dissolution and mass transfer of scCO 2 in water in the sandstone-analogue Micromodel #1 is non-equilibrium, considerably limited by small area-to-volume ratios that represent the pore-throat configurations and characteristics of phase interfaces. Table 2 lists the imposed volumetric injection rates for the four micromodels.…”
Section: Experiments and Imagingmentioning
confidence: 80%
See 2 more Smart Citations
“…Under the experimental conditions (40 °C, 9 MPa), the solubility of scCO 2 dissolved in water is 1.225 mol/L (Spycher and Pruess, 2005). Meanwhile, in previous studies (Chang et al, 2016(Chang et al, , 2017(Chang et al, , 2019, we have showed the dissolution and mass transfer of scCO 2 in water in the sandstone-analogue Micromodel #1 is non-equilibrium, considerably limited by small area-to-volume ratios that represent the pore-throat configurations and characteristics of phase interfaces. Table 2 lists the imposed volumetric injection rates for the four micromodels.…”
Section: Experiments and Imagingmentioning
confidence: 80%
“…This sequence was repeated for a wide range of flow rates. Detailed descriptions of the experimental procedures can be found in Chang et al (2017). Because scCO 2 was continuously injected into the micromodel, the dissolution of scCO 2 in residual water during drainage may have negligible effects on CO 2 saturation and distribution in the pore network.…”
Section: Experiments and Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Their work also indicated that even though the two‐pore network model (pore doublet model) [ Chatzis and Dullien , ] can well describe snap‐off mechanism, it fails in describing the bypass trapping when considering the fluid distribution. Later, the effects of Ca [ Chatzis et al ., ; Soroush et al ., ; Kimbrel et al ., ] and pore structure [ Tanino and Blunt , ; Chaudhary et al ., ; Geistlinger et al ., ] on immiscible flow and capillary trapping were extensively investigated using advanced visualization technology, including X‐ray computed tomography core‐flooding experiments [ Krevor et al ., ; Pentland et al ., ; El‐Maghraby and Blunt , ; Iglauer et al ., ; Andrew et al ., ; Geistlinger et al ., ; Xu et al ., ; Zuo and Benson , ; Li et al ., ; Niu et al ., ; Khishvand et al ., ; Rahman et al ., ; Herring et al ., , ], and micromodel experiments [ Zhang et al ., , ; Wang et al ., ; Kazemifar et al ., ; Cao et al ., ; Chang et al ., , ; Zhao et al ., ]. These studies indicated that (1) at Ca on the order of 10 −7 or even smaller, the snap‐off trapping mechanism by the precursor‐thin film dominates, and it is enhanced by the roughness of pore surface and the throat‐body aspect ratio of pores; (2) at Ca > 10 −7 , the main trapping mechanism involves propagation of invading fluid fingers that lead to islands of defending fluid being bypassed.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of our micromodels is that they can withstand up to 10 MPa pressure drop. The widely used overburden pressure cell [ Zhang et al ., , ; Wang et al ., ; Chang et al ., , ; Jimenez‐Martínez et al ., ] is not needed in our experiment system, allowing us to directly record immiscible displacement behavior at the pore scale without using dyes to enhance the difference of fluorescent signal intensity between scCO 2 and brine phases. Our micromodels exhibited no significant changes in contact angles before and after experiments and retained relatively uniform spatially distributed wettability (see Figure and supporting information Figures S1–S5).…”
Section: Introductionmentioning
confidence: 99%